Distribuição dos casos de leishmaniose visceral e possíveis fatores que influenciam na sua ocorrência no Estado da Paraíba, Brasil - Silva , Allan Batista (2019)
Visceral leishmaniasis (LV) is an infectious parasitic disease caused by the protozoan of the genus Leishmania. Taken as a neglected disease and considered a serious global public health problem, LV has been showing changes in its transmission pattern in recent years, with records of expansion to non-endemic areas. Despite this, there are gaps in the scientific knowledge about LV in the state of Paraíba. For this reason, the present study aimed to analyze the distribution of LV and the possible factors that influence its occurrence in the state of Paraíba between 2012 and 2017. It is an ecological study, developed during the period from September 2017 to August of 2018, in which the sample was composed of 64 municipalities. The information was collected in the database of the Central Laboratory of Public Health Dr. Telma Lobo - PB and Atlas of Human Development in Brazil. The negative binomial regression model was applied to analyze which of the auxiliary variables under study are important to explain the number of cases of human visceral leishmaniasis (LVH) in the state. The results revealed that between 2012 and 2017, 327 cases of LVH and 6,353 cases of canine visceral leishmaniasis (LVC) were confirmed, respectively. LVH showed an increase in its percentage of positivity over the analyzed period, reaching in 2017 the highest percentage of the disease (27.15%). The LVC showed the highest percentage of positivity in Paraíba, registering a value of 58.56% of the cases investigated. However, there was a reduction of this percentage from 2015. At the municipal level, it was also observed that over the years the LVH and LVC showed expansion in the state. The negative binomial regression model adjusted for the number of LVH cases in the State of Paraíba, showed the following variables as significant: number of LVC cases, number of inhabitants, municipal human development index, per capita income, percentage of poor, percentage of children in homes where no one has a primary education, percentage of children 0 to 5 years out of school, percentage of children from 6 to 14 years out of school, percentage of the population in domiciles with running water, percentage of the population in households with garbage collection, percentage of people in households with water supply and inadequate sewage, belong to the Intermediate Geographical Region of Campina Grande. The negative binomial regression model developed showed that the selected model can be used as a reference to analyze the LV distribution and the possible factors that influence its occurrence in the state. In view of the above, it is clear the importance of municipal managers to carry out more frequent, persistent and effective disease control / prevention measures. Since these activities should not be limited to the health sector of the municipality, but also to others, such as social, economic and housing.